Assessment of Knowledge about Obstetric Danger Signs and Associated Factors among Pregnant Women in Debre Tabor Town, Northwest Ethiopia - Mestawut Mihret; Hailegebriel Wondimu (Hindawi Limited, 2023)
Background. World Health Organization estimates that 800 women die from pregnancy or childbirth-related complications around the world every day. With the assumption that "every pregnancy faces risk" women should be aware of the danger signs of obstetric complications during pregnancy, delivery, and postpartum. Indications on the prevalence of obstetric danger signs and risk factors were crucial in designing programs at different levels in reducing maternal morbidity and mortality. Objective. To assess the knowledge about obstetric danger signs and associated factors among pregnant women in Debre Tabor town, Northwest Ethiopia, 2021. Methods. A community-based cross-sectional study was conducted with 295 respondents to assess knowledge about obstetrical danger signs among pregnant women in Debre Tabor town from July to September 2021. Data were collected through self-administered questionnaires. Proportional followed by simple random sampling was used to select the study participants among the pregnant women in each of the six kebeles of the town. Adjusted odds ratios at 95% confidence interval and a value of p<0.05 were used to identify the predictors. Results. From a total of 295 interviewed, 61% of them were poorly knowledgeable about obstetric danger signs, but 39% of them were knowledgeable. According to our study, maternal age less than or equal to 30 years (adjusted odds ratio=5.44; 95% confidence interval: 3.26,9.10), no formal education (adjusted odds ratio=9.488; 95% confidence interval: 4.73, 13.14), one-time gravidity (adjusted odds ratio=7.81; 95% confidence interval: 4.79, 9.19), and frequency of antenatal follow-up less than 4 times (adjusted odds ratio=4.10; 95% confidence interval: 1.88, 8.96) were factors which significantly associated with the poor knowledge of obstetric danger signs. Conclusion. As the knowledge of pregnant women towards obstetric danger signs was low, maternal age less than or equal to 30 years, no formal education, one-time gravidity, and less than 4 times the frequency of antenatal follow-up are associated factors for poor knowledge on obstetric danger signs.